![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
(2x+3y-5)(2x-3y-5)求解
5个回答
展开全部
(2x+3y-5)(2x-3y-5)
=(2x-5)²-9y²
=(2x-5)²-9y²
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
(2x+3y-5)(2x-3y-5)
=[(2x-5)+3y][(2x-5)-3y]
=(2x-5)^2-(3y) ^2
=4x^2-9y^2 -20x+25
=[(2x-5)+3y][(2x-5)-3y]
=(2x-5)^2-(3y) ^2
=4x^2-9y^2 -20x+25
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
(2x+3y-5)(2x-3y-5)
=[(2x+3y)-5][(2x-3y)-5]
=(2x+3y)(2x-3y) -5(2x+3y)-5(2x-3y) +25
=4x^2-9y^2 -20x+25
=[(2x+3y)-5][(2x-3y)-5]
=(2x+3y)(2x-3y) -5(2x+3y)-5(2x-3y) +25
=4x^2-9y^2 -20x+25
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询